PROBLEMATIKA DAN PERLINDUNGAN HUKUM E-COMMERCE DI INDONESIA - Erie Hariyanto (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
One of the developments of information technology, telecommunication and computer is appearing the creation of transaction model that is not necessary to meet directly or face to face. The transaction is enough to do by using the electronic media that is internet media. In the transaction of e-commerce, many law problems develop that need a law arrangement briefly and clearly as a guarantee of the law protection for the people involved. This article tries to answer this problem by giving some alternative solutions in order to make the assurance law in e-commerce transaction formed.